1993
DOI: 10.2307/3578464
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Associated Lung Cancer: A Comparison of the Histology of Lung Cancers in Uranium Miners and Survivors of the Atomic Bombings of Hiroshima and Nagasaki

Abstract: A binational panel of Japanese and American pulmonary pathologists reviewed tissue slides of lung cancer cases diagnosed among Japanese A-bomb survivors and American uranium miners and classified the cases according to histological subtype. Blind reviews were completed on slides from 92 uranium miners and 108 A-bomb survivors, without knowledge of population, sex, age, smoking history, or level of radiation exposure. Consensus diagnoses were obtained with respect to principal subtype, including squamous-cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 12 publications
0
21
1
1
Order By: Relevance
“…A similar result was reported in a Chinese study among tin miners, 22 as well as in Japanese uranium miners and atomic bomb survivors. 28 In comparison with the average exposure to radon progeny (around 500 WLM) of the miners enrolled by Kreuzer et al 1 during 1991-1995, the exposure level of our study group was higher (around 800 WLM). Kreuzer et al 1 used the 25% percentile and 75% percentile of the WLM distribution for defining low exposure (Ͻ 43 WLM) and high exposure (Ն 900 WLM).…”
Section: Discussioncontrasting
confidence: 54%
“…A similar result was reported in a Chinese study among tin miners, 22 as well as in Japanese uranium miners and atomic bomb survivors. 28 In comparison with the average exposure to radon progeny (around 500 WLM) of the miners enrolled by Kreuzer et al 1 during 1991-1995, the exposure level of our study group was higher (around 800 WLM). Kreuzer et al 1 used the 25% percentile and 75% percentile of the WLM distribution for defining low exposure (Ͻ 43 WLM) and high exposure (Ն 900 WLM).…”
Section: Discussioncontrasting
confidence: 54%
“…However, it has been reported that a rectal SCC developed several years after pelvic radiation therapy, 56 and small cell lung cancer was the most frequent subtype of lung cancer among Japanese atomic bomb survivors. 57 It is worth noting that no previous history of well-differentiated NEC that turned into a poorly differentiated cancer, suggestive of a dedifferentiation process, was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Dans le cas des bombes atomiques, la population a été irradiée par les rayons y e t les neutrons ; l'irradiation a été de très courte durée, externe, uniformément répartie sur l'ensemble de l'appareil respiratoire. Au contraire, dans le cas du radon, l'irradiation est de type a, de longue durée, interne, localisée (Land et al, 1993 ;Shigematsu et al, 1995). Les études épidémiologiques pourront bientôt profiter des travaux de Lubin et al, qui sont en cours d'évaluation, et qui portent sur 68000 mineurs et 2700 cancers (les analyses du BEIR IV avaient porté sur un échantillon nettement plus petit, comprenant 22 190 mineurs et 360 cancers ; Lubin, 1994).…”
Section: Discussionunclassified